Meaning-making in literature : unlocking stances and perspectives of ESL readers - Tina Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Meaning-making in reading literary texts is a process that is widely theorised, applied in instructions, and observed through research. While recognitions have been given to the value of literature for different purposes, trends in educational policies for literature in different curricula do not secure a clear and systematic way of how meaning-making should be explored. Research into meaning-making demonstrates the need to examine the process as this remains to be understudied. This study observed the meaning-making process through the stances and perspectives adopted among a group of ESL readers when meaning was made in reading a literary text. This case study employed Concurrent Verbal protocol for data collection. 31 participants, majoring in Teaching English as a Second language (TESL) were selected for the study. Qualitative data from the verbal protocol sessions were quantified using a preestablished set of 24 themes derived from the theoretical framework of the study. The themes were based on the Efferent, Aesthetic, and Critical stances and also the public and private perspectives of the Text, Reader, Universal Values, and Writer. The findings indicate that the Critical is favoured over the Efferent and Aesthetic stances. Public Textual Perspectives were also preferred over the Private Textual, Reader, Universal, and Writer’s perspectives. The implication of examining the meaning-making process from multiple perspectives would nurture learning aptitudes and encourage personal connection and engagement to literature. Future research should consider expanding the investigation into the meaning-making process on other categories of readers as well as literary genres.